BECOMING KCNA CERTIFIED build a strong foundation in cloud native and Kubernetes and pass the KCNA exam with ease - Galkin, Dmitry (Packt Publishing Ltd., 2023)
Kick-start your learning journey and implement both Kubernetes and cloud-native technologies in real-life scenarios with this essential, practical guide to the KCNA exam Purchase of the print or Kindle book includes a free PDF eBook Key Features Gain an in-depth understanding of cloud-native computing and Kubernetes concepts Prepare for the KCNA exam with the help of practical examples and mock exams Manage your applications better with Kubernetes container orchestration Book Description The job market related to the cloud and cloud-native technologies is both growing and becoming increasingly competitive, making certifications like KCNA a great way to stand out from the crowd and learn about the latest advancements in cloud technologies. Becoming KCNA Certified doesn't just give you the practical skills needed to deploy and connect applications in Kubernetes, but it also prepares you to pass the Kubernetes and Cloud Native Associate (KCNA) exam on your first attempt. The book starts by introducing you to cloud-native computing, containers, and Kubernetes through practical examples, allowing you to test the theory out for yourself. You'll learn how to configure and provide storage for your Kubernetes-managed applications and explore the principles of modern cloud-native architecture and application delivery, giving you a well-rounded view of the subject. Once you've been through the theoretical and practical aspects of the book, you'll get the chance to test what you've learnt with two mock exams, with explanations of the answers, so you'll be well-prepared to appear for the KCNA exam. By the end of this Kubernetes book, you'll have everything you need to pass the KCNA exam and forge a career in Kubernetes and cloud-native computing. What you will learn Get to grips with Cloud Native Computing Foundation (CNCF) and its projects Build, configure, and run containers with Docker Bootstrap minimal Kubernetes clusters for learning Manage and encrypt container traffic with Service Mesh Deploy, configure, and update applications on Kubernetes Control and connect the applications that run on Kubernetes Manage storage and provide observability on Kubernetes Automate software development with CI/CD and GitOps Who this book is for This book is for DevOps engineers, system administrators, developers, fresh IT graduates, or anyone interested in cloud native architecture, applications, and technologies. Those with relevant work experience looking to upskill themselves in order to manage their applications with Kubernetes in a better way will also find this book helpful. Familiarity with IT fundamentals, networks, and command line interface (CLI) is required, but no prior knowledge of Kubernetes, docker, or cloud services is needed to get started with this book.